2022
DOI: 10.3390/plants11141819
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Yield Components and Desirable Eating Quality of Two Wheat Genotypes Using Si and NanoSi Particles under Heat Stress

Abstract: Global climate change is a significant challenge that will significantly lower crop yield and staple grain quality. The present investigation was conducted to assess the effects of the foliar application of either Si (1.5 mM) or Si nanoparticles (1.66 mM) on the yield and grain quality attributes of two wheat genotypes (Triticum aestivum L.), cv. Shandweel 1 and cv. Gemmeiza 9, planted at normal sowing date and late sowing date (heat stress). Si and Si nanoparticles markedly mitigated the observed decline in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 128 publications
2
3
1
Order By: Relevance
“…The potassium content was significantly decreased only in plots receiving the Si and Si + S treatments compared to the control, the S treatment did not change the K content. This partially contradicts the results of Helal et al [ 30 ], who observed an increase in the Ca, P, and Zn contents with Si treatment in two wheat cultivars. The Zn content was relatively low (11.921–17.083 mg kg −1 ) compared to the findings of other researchers [ 35 , 36 , 37 , 38 ], which was probably caused by the low Zn content (1.84–2.77 mg kg −1 ) in the soil of the experiment area.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The potassium content was significantly decreased only in plots receiving the Si and Si + S treatments compared to the control, the S treatment did not change the K content. This partially contradicts the results of Helal et al [ 30 ], who observed an increase in the Ca, P, and Zn contents with Si treatment in two wheat cultivars. The Zn content was relatively low (11.921–17.083 mg kg −1 ) compared to the findings of other researchers [ 35 , 36 , 37 , 38 ], which was probably caused by the low Zn content (1.84–2.77 mg kg −1 ) in the soil of the experiment area.…”
Section: Discussioncontrasting
confidence: 98%
“…Gell et al [ 7 ] found that for the 180 oat varieties they analysed, the protein content of samples of the same variety could vary by 15 percent with water availability. Studies on Si [ 30 ] and S-treatments [ 31 , 32 ] report that protein content generally increases as a result of the treatment. The results of Helal et al [ 30 ] confirm this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best interaction was spraying with nano-silicon (300 mg/L) on transplanting date at 1 st March. These findings are in harmony with those obtained by Helal et al (2022) who reported that Si nanoparticles were planted at normal sowing dates and late sowing dates (heat stress) and that these treatments significantly reduced the observed decline in yield and the heat stress intensity index value at late sowing dates as well as enhanced wheat yield quality. Accordingly, it is possible that the increased fruit yield per plant, total fruit yield per plant, and average fruit weight in this study are caused by the nano silicon which is one of the elements that helps plants become more resistant to heat stress Saber et al (2021).…”
Section: Yield and Physical Fruit Characterssupporting
confidence: 91%
“…Shandweel 1 and cv. Gemmeiza 9 by alleviating the decrease in grain yield and preserved their nutritional values (increased protein content and reduced α-amylase activity) . Silica NPs applied via leaves to thale cress were shown to enter through stomata and exert salicylic acid-dependent systemic acquired resistance against Pseudomonas syringae; notably, silica NPs were shown to be safer than direct orthosilicic acid-OSA application because of the slow release of OSA and the lower eco- and phytotoxicity …”
Section: Introductionmentioning
confidence: 99%